2015
DOI: 10.1037/pspi0000022
|View full text |Cite
|
Sign up to set email alerts
|

Building social resilience in soldiers: A double dissociative randomized controlled study.

Abstract: Can social resilience be trained? We report results of a double-dissociative randomized controlled study in which 48 Army platoons were randomly assigned to social resilience training (intervention condition) or cultural awareness training (active control group). The same surveys were administered to all platoons at baseline and after the completion of training to determine the short-term training effects, generalization effects beyond training, and possible adverse effects. Multilevel modeling analyses indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 92 publications
3
46
0
2
Order By: Relevance
“…Of these 226 Cadets, 215 (95.13%) consented to being involved in the SRT evaluation (16.9% females; 83.1% males). This rate of initial consent is comparable to other resilience training evaluations conducted within the Army (e.g., Cacioppo, et al, 2015).…”
Section: Participants and Designsupporting
confidence: 74%
See 1 more Smart Citation
“…Of these 226 Cadets, 215 (95.13%) consented to being involved in the SRT evaluation (16.9% females; 83.1% males). This rate of initial consent is comparable to other resilience training evaluations conducted within the Army (e.g., Cacioppo, et al, 2015).…”
Section: Participants and Designsupporting
confidence: 74%
“…A small number of Cadets (6%, n=12) from international militaries (e.g., New Zealand) were also completing second-class at RMC. Assignment to one of the two intervention conditions was randomized by platoon, which is a common practice in military training evaluations in order to avoid crosscontamination of training content (Adler et al, 2009;Cacioppo, et al, 2015). RMC instructors assigned the seven platoons to two groups and were unaware which of the two-groups would receive which training.…”
Section: Participants and Designmentioning
confidence: 99%
“…For example, survivors of childhood sexual abuse who report PTG also report accrued identity benefits, such as improved relationships with others and stronger religious affiliation (Wright, Crawford, & Sebastian, 2007). Relatedly, studies of military personnel have observed that a focus on the collective (rather than the personal) experience of trauma helps both individuals and groups to learn and grow from their traumatic experiences (Cacioppo et al, 2015).…”
Section: Social Identity Gain: Gaining a New Social Identity Reduces mentioning
confidence: 99%
“…It has yielded improvements of basic EP (i.e., face recognition; Kurtz and Richardson, 2011; Kandalaft et al, 2013), as well as of theory of mind and social interaction skills (Turner-Brown et al, 2008; Kandalaft et al, 2013). Similar approaches have proved valid in individuals with Traumatic Stress Disorder (PTSD; Foa, 1997; Foa et al, 2005; Sin and Lyubomirsky, 2009; Akbarian et al, 2015), and also in active military (Castro et al, 2012; Cacioppo et al, 2015) and ex-combatants (Karlin et al, 2010). SCT seems to be a feasible approach to improve emotional recognition in ex-combatants (Kurtz and Richardson, 2011; Tobon et al, 2015; Quintero-Zea et al, 2017).…”
Section: Introductionmentioning
confidence: 99%